2008
DOI: 10.1016/j.matdes.2007.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Finite element and coupled finite element/smooth particle hydrodynamics modeling of the quasi-static crushing of empty and foam-filled single, bitubular and constraint hexagonal- and square-packed aluminum tubes

Abstract: The quasi-static axial crushing behavior of empty and Al and polystyrene foam-filled Al single, bitubular and multi-tube-packed (hexagonal and square packing) configurations were investigated experimentally and numerically. Tubes were modeled using finite element and coupled finite element/smooth particle hydrodynamics. The numerical specific absorbed energy (SAE) values, deformation patterns, load values and number of folds formed were found to show agreements with those of experiments. Among the tested tube … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…After undertaking a convergence study, an element size of 3 mm was found to produce suitable results. The same conclusion had been drawn by Aktay et al [35] in a similar structure. Therefore, the side lengths of square and cube elements in the tube wall and foam were both 3 mm.…”
Section: Finite Element Modelingsupporting
confidence: 86%
“…After undertaking a convergence study, an element size of 3 mm was found to produce suitable results. The same conclusion had been drawn by Aktay et al [35] in a similar structure. Therefore, the side lengths of square and cube elements in the tube wall and foam were both 3 mm.…”
Section: Finite Element Modelingsupporting
confidence: 86%
“…The SAE values of honeycomb filling are further compared ) filling of the same Al tube, which was previously studied [10] tubes, there exists a critical cell size/density of honeycomb above which the filling becomes more efficient than tubewall thickening.…”
Section: Resultsmentioning
confidence: 99%
“…The widespread use of thin-walled tubes as energy absorbers is due to their good performance under dynamic loading, availability, low manufacturing cost, and efficiency. Numerous efforts have been made in the past decades to improve the crashworthiness performance of the crush absorber tubes, such as foam filled tubes (Hanssen et al 2000;Ahmad & Thambiratnam 2009b;2009c;Aktay et al 2008;Mirfendereski et al 2008), introducing different patterns (Zhang et al 2007), grooves (Zhang & Huh 2009;Saleh ghaffari et al 2010), multi-cells (Zhang & Zhang 2013;Zhang & Zhang 2014), and functionally graded structures (Mohammadiha & Ghariblu 2016;Sun et al 2010). Relative merits of conical tubes with graded thickness subjected to oblique impact loads are investigated by Zhang (Zhang & Zahng 2015).…”
Section: Introductionmentioning
confidence: 99%